2016
DOI: 10.1007/s12529-016-9596-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alcohol Use, Sexual Risk Behavior, and HIV Among Russians in High-Risk Settings: a Systematic Review and Meta-Analysis

Abstract: Objective To examine the (a) prevalence of and (b) association between alcohol, risky sex, and HIV among Russians at-risk for primary or secondary HIV transmission. Method Electronic databases were searched to locate studies that sampled Russians, assessed alcohol, and included either a behavioral measure of risk or a biological measure of HIV. Weighted mean (logit) effect sizes were calculated using random-effects assumptions. Moderator analyses were conducted using meta-regression. Results Studies (19) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…In the following, we try to summarize recent developments (following closely [98]; see also [99]), and suggest an operationalization to quantify the causal impact of alcohol use on HIV/AIDS. Alcohol use was found to be associated with HIV incidence and prevalence in systematic reviews and metaanalyses [100][101][102][103][104][105][106]. This association may have resulted, in part, from the causal impact of acute alcohol use on sexual decision-making [107], resulting in condomless sex [105,[108][109][110][111][112][113][114].…”
Section: Hiv/aidsmentioning
confidence: 99%
“…In the following, we try to summarize recent developments (following closely [98]; see also [99]), and suggest an operationalization to quantify the causal impact of alcohol use on HIV/AIDS. Alcohol use was found to be associated with HIV incidence and prevalence in systematic reviews and metaanalyses [100][101][102][103][104][105][106]. This association may have resulted, in part, from the causal impact of acute alcohol use on sexual decision-making [107], resulting in condomless sex [105,[108][109][110][111][112][113][114].…”
Section: Hiv/aidsmentioning
confidence: 99%
“…Condom use was 67% and 25% of the sample reported multiple, concurrent partners [16]. Finally, a recent meta-analysis of alcohol and sexual transmission risk in Russia [17] found that individuals with high levels of alcohol use or "hazardous/harmful alcohol use" reported significantly more sexual partners and less consistent condom use than those who used alcohol recreationally. For a comprehensive review of alcohol and sexual behavior that can lead to HIV transmission, see Freeman [18].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding lifestyle, although diet characteristics have not been previously analyzed in this sense, similar results have been obtained when food insecurity has been related to sexual behavior in adolescents and young adults [ 32 , 33 , 34 ]. Similarly, in the case of alcohol, various previous studies have found a significant positive association between alcohol consumption and HIV risk in young and adult populations [ 56 , 57 , 58 ]. Although smoking was associated, in classical research, with HIV risk [ 23 , 24 , 25 , 26 , 27 ], few studies have been conducted recently.…”
Section: Discussionmentioning
confidence: 83%